A study of the synergistic effects of Mn/steam on CO2 capture performance of CaO by experiment and DFT calculation. Issue 2 (8th March 2019) - Zhang, Wan; Ma, Xiaotong; Li, Yingjie; Zhao, Jianli; Wang, Zeyan
Abstract: Novel Mn‐doped CaO was prepared by the combustion method. The CO2 capture performance of Mn‐doped CaO, carbonated in the presence of steam and under severe calcination conditions (950°C and 70% CO2 /30% N2 ) during calcium looping cycles, was investigated in a dual fixed‐bed reactor. The intercoupling effects of Mn and steam on CO2 capture by CaO were also studied. Doping of Mn in CaO by the combustion method greatly improved the CO2 capture capacity of CaO. The carbonation conversions of Mn‐doped CaO increased with increasing steam concentration from 0 to 15%. When the molar ratio of Mn/Ca was 0.75 : 100, Mn‐doped CaO achieved the highest CO2 capture capacity. Under severe calcination conditions, the carbonation conversion of Mn‐doped CaO, where the molar ratio of Mn to Ca = 0.75 : 100 in the presence of 15% steam, was about 0.4 after ten cycles (carbonation for 5 min at 650°C under 15% CO2 /15% steam/N2 ), which was 4.38 times as high as that of the original CaO in the absence of steam. The cyclic CO2 capture capacities of CaO were improved by Mn and steam. Synergistic enhancement effects of Mn and steam on the CO2 capture capacities of CaO were also found. The effect of steam on the carbonation conversion of Mn‐doped CaO was stronger than that of the original CaO. Mn in the presence of steam showed a more positive effect on CO2 capture by CaO. X‐ray photoelectron spectroscopy analysis showed that doping of Mn in CaO enhanced the transport of electrons in the carbonation of CaO, which helped to increase the carbonation rate. When steam was present in the carbonation, Mn‐doped CaO possessed a more porous structure and smaller CaO grains than the original CaO during the cycles. Simulation calculations using periodic density functional theory (DFT) showed that CO2 molecules were easier to absorb on CaO owing to the doping of Mn and the presence of steam. The synergistic enhancement effects of Mn and steam on CO2 captured the performance of CaO. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.